Prediction and Prevention of Upper Gastrointestinal Bleeding after Cardiac Surgery: A Case Control Study - Mamatha Bhat; Martin Larocque; Marcos Amorim; Karl Herba; Myriam Martel; Benoît De Varennes; Alan Barkun (Canadian Journal of Gastroenterology)
BACKGROUND: Gastrointestinal (GI) complications of cardiovascular surgery, particularly bleeding, occur frequently.